Wrist and hand rehabilitation software platform based on leap motion controller - Postolache, G. (2017)
A software platform based on Leap Motion Controller (LMC) movements’ detection was developed. It allows measurements of clinically proved effective hand and finger exercises. The developed software allows representation of amplitude of each different movement, time interval for each movement, frequency of different movements, asymmetry of bilateral movements, standard deviation of signal amplitude, Poincaré plots. A serious game Collect Color Cube, was developed using Unity, C# scrips, and signals from LMC related to movements of the user’s hands and fingers.